Peeler machine / Aiman Aizuddin Ghazali ...[et al.] - Ghazali, Aiman Aizuddin; Suhaimi, Muhamad Azeem; Wan Zaini, Wan Syafiq; Mohd Noor, Muhammad Faiz; Hasliman, Muhammad Khairul Azmi (2016)
The objective of this project was to study on designing, fabricating and evaluating the Auto Fruit Peeler Machine (AFPM). The new design of this AFPM is very suitable for domestic use because of small size, safety features and lightweight, compared with the similar products that are driven by a motor. Few considerations have been take into establish the appropriate criteria for this AFPM. Among them is the size, portability, and energy-saving. A safety feature is the peeling process is in the container where the user does not contact with the blade. This is a useful machine to automatically peel the fruits. The speed rotation of the fruit can be controlled for energy saving depend on the soft and hard of the fruit skin surface. Peeler products in the current market, is only a hand peeler apparatus. We believe this product can penetrate the market, because it easy to use, added with safety features